Características epidemiológicas de pacientes infectados por el VIH que reciben tratamiento anti retroviral en el Hospital Regional de Loreto - Valdez Seminario, Santiago José (2024)
The Human Immunodeficiency Virus (HIV) infection is a global epidemic with 43 years of evolution and an increase in cases. According to the World Health organization (WHO), by the end of 2021 there were 38.4 million people living with HIV and 650 000 deaths from this infection. In Peru, the first case of Acquired Immunodeficiency Syndrome (AIDS) was described in 1983 by R Patrucco in a young man who had travelled to New York and maintained homosexual relations. (1,8) In Loreto, the HIV epidemy have had a strong impact. It is the second department with the most reported cases of HIV, after Lima. Epidemiologic, social and sexual factors are the main reasons determining the risk for HIV infection. (4) This essay seeks to evaluate the different epidemiological characteristics in people living with HIV that receive antiretroviral treatment to better understand the dynamics of infection, adherence to treatment and disease progression and outcome in the department of Loreto.